2016
DOI: 10.1002/jsfa.7722
|View full text |Cite
|
Sign up to set email alerts
|

Integration of antimicrobial pectin‐based edible coating and active modified atmosphere packaging to preserve the quality and microbial safety of fresh‐cut persimmon (Diospyros kaki Thunb. cv. Rojo Brillante)

Abstract: The combination of the pectin-based edible coating and active MAP proved to be the most effective treatment to maintain the sensory and microbiological quality of persimmon slices for more than 9 days of storage. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Decrease in cell wall enzymes activities might be a probable reason for firmness preservation as stated by Sanchis et al [ 23 ] and Kumar et al [ 24 ] due to ripening delay by coating application [ 6 ]. Polygalacturonase (PG) enzyme is one of the main softening enzymes in plum [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decrease in cell wall enzymes activities might be a probable reason for firmness preservation as stated by Sanchis et al [ 23 ] and Kumar et al [ 24 ] due to ripening delay by coating application [ 6 ]. Polygalacturonase (PG) enzyme is one of the main softening enzymes in plum [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…CMC-based edible coatings have been shown to be efficient in preserving postharvest quality of pear, papaya, mandarin and peach [ 16 , 17 , 18 , 19 ]. Pec-based ones preserved quality of peach, nectarine, fresh-cut apple, and persimmon [ 20 , 21 , 22 , 23 ]. Some studies reported the application of edible coatings on plum fruit, including chitosan [ 24 ], and carboxymethylcellulose, alone [ 8 ] or in combination with irradiation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…By promoting food perspiration, these films also help to reduce enzymatic browning and water loss. Furthermore, this protection may also be enhanced by the addition of other ingredients, such as minerals, antioxidants, nutrients, vitamins or probiotics [109]. On the other hand, when the extraction of solvents at their supercritical state is produced in hydrogels or alcogels, the resultant material is called aerogels.…”
Section: Emulsions and Gelsmentioning
confidence: 99%
“…However, coating with chitosan with no other active agents did not show significant inhibition for these microorganisms. Pectin biopolymers were also used to coat fresh-cut persimmon (Diospyros kaki) [116]. The edible coating was elaborated from a base solution of apple pectin at 10 g/kg emulsified with oleic acid and Tween80, whereas glycerol was added as the plasticizer.…”
Section: Fruits and Vegetablesmentioning
confidence: 99%